Islamic Work Ethics, Local Wisdom, and Spirit of Capitalism: Insight from a Perantau Minangkabau - Mochlasin, Mochlasin; Budiharjo, Budiharjo (Indonesian Journal of Islam and Muslim Societies, 2024)
This study aims to uncover the phenomenon of Islamic work ethics among the Minangkabau diaspora in the Special Region of Yogyakarta. The research adopts a phenomenological approach, utilizing Weber’s theory and the religious dimensions theory proposed by Glock and Stark. To delve into the role of tradition in shaping the spirit of capitalism, Bourdieu’s theory of cultural reproduction is employed. Data collection techniques include literature reviews, field observations, and in-depth interviews with Minangkabau migrants engaged in trading in Yogyakarta. The findings of this research elucidate the phenomenon of the spirit of capitalism among the Minangkabau, which differs from Weber’s conclusions about modern industrial societies in the West. The religious traditions of the Minangkabau community are known to be strong, as reflected in the life philosophy of "Adat Basandi Syarak Syarak Basandi Kitabullah," meaning customs are based on law, and law is based on the Qur’an. In practice, the spirit of capitalism among the Minangkabau is not only inspired by Islamic teachings on economic doctrines but also rooted in local wisdom in the form of proverbs (pepatah-petitih) that have become integrated into speech, attitudes, and actions. The combination of religious teachings and local wisdom gives rise to the spirit of capitalism implemented in trading activities. The family network business model of kinship inspired by the values of local wisdom is also an interesting finding regarding the resilience and sustainability of their businesses. This research emphasizes the significant contribution of religious teachings and local values to the spirit of capitalism, a factor that has been overlooked. Practically, it can be useful in advocating for the preservation of local wisdom as a positive source of wealth amid the infiltration of modern culture in the era of digitization.